PENERAPAN METODE SIMPLE MULTI-ATTRIBUTE RATING TECHNIQUE EXPLOITING RANK (SMARTER) DALAM PEMILIHAN BIBIT UNGGUL JAGUNG DI DESA SILAU MANGI - Irena Blaster; Riri Syafitri Lubis; Nenna Irsa Syahputri (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2023)
Agriculture is one of the important sectors in Indonesia. Most of Indonesia's population depends on the agricultural sector, one of which is corn farmers. Cultivation of corn plants starts from choosing quality seeds. Determination of quality corn seeds aims to increase productivity and quality of production. Various efforts can be made to increase corn production such as the use of superior corn seeds. Efforts to increase corn production are still experiencing several obstacles, such as the lack of understanding of farmers in determining superior corn seeds. This study aims to apply the SMARTER method in selecting superior maize seeds in order to increase maize production. The Simple Multi Attribute Rating Technique Exploiting Rank (SMARTER) method is one of the methods in a decision support system whose solution is by using Rank Order Centroid (ROC) weighting on each criteria and sub-criteria. The results of the research carried out obtained five criteria that were used as an assessment in the selection of corn seeds, namely resistance to pests, seed size, production yield, environmental adaptation and harvest time